Waiting for kin: a longitudinal study of family reunification and refugee mental health in Germany - Lea-Maria Löbel; Jannes Jacobsen (Journal of Ethnic and Migration Studies, 2021)
Involuntarily or planned – many refugees flee their home country alone, leave behind spouses and children but also siblings, parents and other family members they otherwise care for. Reunification in hosting communities is difficult, as governments limit institutional family reunifications and the individual journey of kin is dangerous and often illegal. Having family abroad is mentally distressing for refugees, as kin might not live in safety. Additionally, reuniting with family members can be a source of support in the new environment. Grounded in theories of mental distress and social support, this analysis investigates the association between family reunifications and refugee mental health in a random sample of refugees in Germany (N0.167em=0.167em6610), the IAB-BAMF-SOEP Survey of Refugees 2016–2018. By means of panel fixed-effect regression analysis, we observe institutionally sponsored but also individual moves of other family members. The study finds that family reunification has a positive association with refugee mental health, though not at an equally increasing rate for each additional member of the family. Gender differences show in the size of association, yet significant heterogeneous associations between refugee men and women cannot be observed. Finally, the associations are larger when only observing reunifications with the nuclear family.
Keywords: 330; Refugees; Family reunification; Mental health; Social support; Gender